Ibn battuta : travels in asia and africa 1325-1354 - Gibb, A. R.; Gibb, H. A. R. ([S.l.] : South Asia Books, 1984)
In this book the author lays before the reader a faithful portrait of himself, with all his virtues and his failings and gives full account of his wide spread travel through many countries of medieval Asia and Africa. This book a classic in its genre is indispensable for scholars of medieval history.